Treatment Integrity Failures during Timeout from Play. Issue 6 (November 2021) - Foreman, Apral P.; Peter, Claire C. St.; Mesches, Gabrielle A.; Robinson, Nicole; Romano, Lucie M.
Timeout is an effective behavior-reduction strategy with considerable generality. However, little is known about how timeout is implemented under natural conditions, or how errors in implementation impact effectiveness. During Experiment 1, we observed teachers implementing timeout during play to evaluate how frequently the teachers implemented timeout following target behavior (omission errors) and other behaviors (commission errors) for four children. Teachers rarely implemented timeout; thus, omission errors were frequent, but commission errors rarely occurred. During Experiment 2, we used a reversal design to compare timeout implemented with 0% omission integrity, 100% integrity, and the level of omission integrity observed to occur during Experiment 1 for two of the participants. Timeout implemented with reduced-integrity decreased problem behavior relative to baseline, suggesting that infrequent teacher implementation of timeout may have been sufficient to reduce problem behavior.